Photochirogenic nanosponges: phase-controlled enantiodifferentiating photoisomerization of (Z)-cyclooctene sensitized by pyromellitate-crosslinked linear maltodextrin. Issue 28 (20th March 2017) - Liang, Wenting; Zhao, Meiling; Wei, Xueqin; Yan, Zhiqiang; Wu, Wanhua; Caldera, Fabrizio; Trotta, Francesco; Inoue, Yoshihisa; Su, Dan; Zhong, Zhihui; Yang, Cheng
Abstract : The enantioselectivity of the photoisomerization of ( Z )-cyclooctene sensitized by the linear maltodextrin-based nanosponges are critically dependent on the phase properties. Abstract : Linear maltodextrin (LM) was cross-linked by pyromellitic dianhydride to afford LM polymers of different cross-linking degrees. When soaked in water, these cross-linked LM polymers (nanosponges (NSs)), evolved into several phases from sol to suspension, then to flowing gel, and finally to rigid gel with an increase in their content. Enantiodifferentiating photoisomerization of ( Z )-cyclooctene (1Z ) to chiral ( E )-isomer (1E ), which was employed as a benchmark reaction to quantitatively assess the environmental-to-molecular chirality transfer process, was performed in aqueous media containing these pyromellitate-crosslinked LM-NSs in different phases. The enantiomeric excess (ee) of1E obtained was relatively insensitive to the phases at least up to the flowing gel phase, but became highly sensitive in the rigid gel phase, exhibiting an abrupt drop in the early rigid gel phase followed by a rapid recovery in the late rigid gel phase. A comparison with the phase-dependent ee profiles previously reported for similar pyromellitate-crosslinked cyclodextrin (CD)- and cyclic nigerosylnigerose (CNN)-NSs revealed that the chiral void space created around the pyromellitate linker in NS is responsible for the dramatic changes in ee in the rigid gel phase, whereas the inherent host cavity in CD/CNN plays only limited roles in the supramolecular photochirogenesis mediated by the sensitizer-crosslinked NSs. The latter insight allows us to further expand the applicable range of the present concept and methodology by employing a much wider variety of oligosaccharides as well as substrates and sensitizing cross-linkers.